PROPER USE OF CHEMICAL REAGENTS IN TEACHING CHEMISTRY - Khodzhanazarova, Nilufar (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2025)
Teaching chemistry is not only about imparting theoretical knowledge but also about developing practical skills, as it is an experimental science. Chemical reagents play a crucial role as the primary tools for conducting chemical experiments and reactions. The quality, properties, and proper usage of these reagents determine the success and effectiveness of experiments